ExoY from Pseudomonas aeruginosa is a nucleotidyl cyclase with preference for cGMP and cUMP formation - Beckert, Urike (Biochem Biophys Res Commun, 2014)
In addition to the well known second messengers cAMP and cGMP, mammalian cells contain the cyclic pyrimidine nucleotides cCMP and cUMP. Soluble guanylyl cyclase and soluble adenylyl cyclase produce all four cNMPs. Several bacterial toxins exploit mammalian cyclic nucleotide signaling. The type III secretion protein ExoY from Pseudomonas aeruginosa induces severe lung damage and effectively produces cGMP. Here, we show that transfection of mammalian cells with ExoY or infection with ExoY-expressing P. aeruginosa not only massively increases cGMP but also cUMP levels. In contrast, the structurally related CyaA from Bordetella pertussis and edema factor from Bacillus anthracis exhibit a striking preference for cAMP increases. Thus, ExoY is a nucleotidyl cyclase with preference for cGMP and cUMP production. The differential effects of bacterial toxins on cNMP levels suggest that cUMP plays a distinct second messenger role.